Some research perspectives on emissions from bio-mechanical treatments of municipal solid waste in Europe - Rada, E C (Environmental technology, 2005)
The bio-mechanical treatment of Municipal Solid Waste is an increasing option in Europe either as a pre-treatment before landfilling or as a pre-treatment before combustion. The present work deals with the problem of assessment of significant data related to emissions to air from bio-mechanical treatments. Reliable data are necessary for the development of: a) Life Cycle Assessment studies; b) verification of compliance with existing regulations; c) environmental impact studies assessment. In order to point out some lack of knowledge about bio-mechanical treatments, some results of a Life Cycle Assessment study on Municipal Solid Waste bio-stabilization treatment have been reported and analysed. Indeed, during the development of that Life Cycle Assessment, some problems were found regarding the availability and the quality of emission data from Municipal Solid Waste mechanical biological treatment. Concerning existing regulations, in Europe we can find both countries with enhanced approaches, and countries with a soft approach. In the second case, for instance, a few Italian regions adopted local regulations in order to improve the quality of the environmental regulation as the national one has been considered inadequate. The environmental impact assessment of bio-mechanical treatments is not still as developed as options such as incineration. The reason is that the impact of a bio-mechanical treatment plant is considered low. On the contrary it can be demonstrated that a greater attention must be paid in the case of non optimised technologies and large plants